STRATEGI KOMUNIKASI PEMASARAN USAHA KECIL DAN MENENGAH (UKM) GAHARU PLAZA INDONESIA DALAM MENINGKATKAN PENJUALAN PRODUK - Putri Ayu Pangestu; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Economic growth is one of them is marked by the growing world of business in all fields. One of the efforts to expand employment is by developing the Small and Medium Enterprises (SME) sector. The importance of small and medium enterprises (SMEs) that grow in the community can help and show higher resilience and become a buffer of community life. In this case the researcher focuses on marketing strategy of SMEs Gaharu Plaza Indonesia in increasing product sales. This study aims to find out marketing communication strategy implemented by Garuda Plaza Indonesia based on the implementation of marketing communication consisting of sales face to face, sales promotion, direct marketing,public relation conducted. This research was conducted at Gaharu Plaza Indonesia Pekanbaru. This research uses descriptive qualitative method, with purposive technique. In this study selected 1 person from the director, 1 person from the vice director, 1 person from the public relations division and 5 informants from the selected consumer using accidental sampling technique. Data collection techniques used were interviews, observation and documentation. Based on the research that has been done, it is known that marketing communication communication strategy implemented by Garuda Plaza Indonesia SMEs include face-to-face sales conducted SMEs Gaharu Plaza Indonesia with prospective customers at outlets and outside the outlet. Sales promotion is to provide free products and get a discount. Direct marketing directly conducted by SMEs Gaharu Plaza Indonesia by using the phone directly provide information to consumers. Community relations activities conducted by SMEs Gaharu Plaza Indonesia in increasing product sales is to promote products, establish good relationships to consumers and other external parties.Keyword: Marketing Communication Strategy, Product, Small And Medium Enterprises (Smes)